2019
DOI: 10.3390/cancers11010113
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of High-Grade Tumor Budding in Pancreatic Ductal Adenocarcinoma: A Systematic Review and Meta-Analysis with a Focus on Epithelial to Mesenchymal Transition

Abstract: This study aims at clarifying the prognostic role of high-grade tumor budding (TB) in pancreatic ductal adenocarcinoma (PDAC) with the first systematic review and meta-analysis on this topic. Furthermore, we analyzed with a systematic review the relationship between TB and a recently suggested TB-associated mechanism: the epithelial to mesenchymal transition (EMT). Analyzing a total of 613 patients, 251 of them (40.9%) with high grade-TB, we found an increased risk of all-cause mortality (RR, 1.46; 95% CI, 1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 44 publications
1
52
0
Order By: Relevance
“…Recent evidences suggest that tumor budding could represent one of the morphological hallmarks of EMT [20,21]. This hypothesis has been recently confirmed by a meta-analysis [22] that investigated the prognostic role of tumor budding and its relationship with the presence of EMT. Authors concluded that high tumor budding is a risk factor for all-cause mortality and they also confirmed that tumor budding is a morphological aspect intimately associated with EMT [22].…”
Section: Not Investigated In Clinical Studiesmentioning
confidence: 75%
“…Recent evidences suggest that tumor budding could represent one of the morphological hallmarks of EMT [20,21]. This hypothesis has been recently confirmed by a meta-analysis [22] that investigated the prognostic role of tumor budding and its relationship with the presence of EMT. Authors concluded that high tumor budding is a risk factor for all-cause mortality and they also confirmed that tumor budding is a morphological aspect intimately associated with EMT [22].…”
Section: Not Investigated In Clinical Studiesmentioning
confidence: 75%
“…In PDAC, tumor-budding cells and adjacent stromal cells showed increased levels of the E-cadherin repressors ZEB1, ZEB2, and SNAIL1. Moreover, tumor-budding cells lose expression for membrane adhesion molecule E-cadherin and β-catenin, without detectable nuclear β-catenin, and favorize tumor budding detachment from the primary tumor [56]. High expression of ZEB1 in tumor-budding and stromal cells was correlated with high peritumoral invasion.…”
Section: Cd36 Promotes Tumor Metastasis In Pancreatic Cancermentioning
confidence: 94%
“…EMT is a biological process in which the epithelial elements lose their polarity and cell-to-cell contacts, undergo cytoskeleton remodeling with morphological modifications, and acquire migratory capacity [11]. EMT has recently emerged as a crucial biological mechanism in undifferentiated carcinomas of other organs [12,13], and in PDAC has been strongly associated to poor prognosis [14][15][16].…”
Section: Introductionmentioning
confidence: 99%